A Study of the Definitions and Characteristics and Development of a Growth Mindset and Grit Measurement Scale for Pre-service Teachers - Medtajit, Kanokkorn; Aeamtussana, Thammachot; Chularut, Pasana (Ratchaphruek Journal, 2025)
This study aimed to 1) define and characterize growth mindset and grit among pre-service teachers, and 2) develop a Growth Mindset and Grit Measurement Scale tailored to this group. A qualitative approach was employed, involving a comprehensive review of relevant literature and in-depth interviews with five experts in psychology. The data collected were used to construct and assess the content validity and reliability of the measurement instruments. The findings indicate that a growth mindset in pre-service teachers refers to their belief that the ability to manage learning and support students can be continuously developed. It comprises 10 characteristics, including belief in self-growth, commitment to lifelong learning, openness to new experiences, courage in facing challenges, and willingness to collaborate with others. Grit, in the context of pre-service teachers, refers to a strong passion for the teaching profession, a deep commitment to educational goals, and the perseverance to overcome challenges. It consists of two components: passion (commitment to goals and enthusiasm for teaching) and perseverance (resilience and effective problem-solving). The Growth Mindset Measurement Scale consists of 40 items covering 10 characteristics, with a reliability coefficient of 0.91 and item-total correlation ranging from 0.32 to 0.69. The Grit Measurement Scale includes 40 items across 8 characteristics, with a reliability coefficient of 0.94 and item-total correlation ranging from 0.38 to 0.77.